Biomechanical Analysis of TAEKWONDO ‘Geodeup Yeopchagi’ Kick - Heo, Bo-seob; Lee, Hyo-taek; Lee, Jeong-ki (International Journal of Martial Arts , 4(2), 2019)
The purpose of this study was to analyze the movements of the lower extremity joints during a taekwondo kick motion called 'Geodeup Yeopchagi', which was administered to players to improve their balance, stability, and range of motion for the prevention of injuries. The subjects of this study were eight selected skilled practitioners and eight unskilled athletes who had won the national competition from the Poomsae athletes who have been registered with the Korea Taekwondo Association for more than three years. Before entering the experiment, each subject was asked for consent and explained how to proceed with the experiment. Kinematic data were collected by four real-time infrared cameras. The hip joint, knee joint, and ankle joint angles were measured using instruments. Data processing: The statistical process of this study calculated the mean and standard deviation(M ± SD) using Excel 2018, and the statistical program(SPSS 22.0, SPSS Inc., Chicago, IL, USA). The Shapiro-Wilk test was conducted to verify the normality of the collected data. Independent t-test was performed to analyze the effects on the kinematic variables according to the kicks of Taekwondo Poomsae athletes and amateur. test and assay(Mann-Whitney U test) were performed and the significance level of all statistics was set to α = .05. During the 'Geodeup Yeopchagi' kick motion, there were small and inconsistent effects on each joint. The results showed that the characteristics of the poomsae are to balance the feet when hitting the side kick close to 170 degrees quickly and to maintain the CoM close to the base and to support the side kick in order to contribute to the stability of the whole body. We indicated that is correct footing is an important factor in minimizing the next deduction factor. This comparative analysis of the taekwondo kicking motion is considered a very valuable study that can provide important information to the training site or school site. Further studies are needed to analyze the difference between the success and failure of the next kick, the required muscle activity, and the various and instantaneous speed of the center of gravity. KCI Citation Count: 4